2023
DOI: 10.1111/ceo.14262
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on ophthalmic conditions: A scoping review

Noah Heilenbach,
Galen Hu,
Ryan Lamrani
et al.

Abstract: BackgroundEnvironmental factors have been implicated in various eye pathologies. The purpose of this review is to synthesise the published research on environmental effects on eye disease.MethodsFour databases were searched for terms relating to environmental exposures and ophthalmic disease. Titles and abstracts were screened followed by full‐text review. Data was extracted from 118 included studies. Quality assessment was conducted for each study.ResultsAir pollutants, including nitrogen dioxide, nitrites, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 145 publications
0
1
0
Order By: Relevance
“…The public workshop series hosted by the National Academies of Sciences, Engineering, and Medicine in November 2023 named the health research priorities for the East Palestine hazardous materials’ release and named eye irritation as a commonly reported symptom [ 32 ]. Sanchez et al found that veterans exposed to burning oil fields also exhibited more signs of dry eye disease, and smoke from other types of burn and fire situations is also a culprit [ 33 , 34 ] The ophthalmology community has long recognized the importance of dry eye disease as a result of eye irritation, and it is a frequent topic among clinicians and in the ophthalmology literature [ 35 , 36 , 37 ]. There are multiple FDA-approved prescription drugs and over-the-counter artificial tear formulations designed to treat dry eyes [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The public workshop series hosted by the National Academies of Sciences, Engineering, and Medicine in November 2023 named the health research priorities for the East Palestine hazardous materials’ release and named eye irritation as a commonly reported symptom [ 32 ]. Sanchez et al found that veterans exposed to burning oil fields also exhibited more signs of dry eye disease, and smoke from other types of burn and fire situations is also a culprit [ 33 , 34 ] The ophthalmology community has long recognized the importance of dry eye disease as a result of eye irritation, and it is a frequent topic among clinicians and in the ophthalmology literature [ 35 , 36 , 37 ]. There are multiple FDA-approved prescription drugs and over-the-counter artificial tear formulations designed to treat dry eyes [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%